Digital Monitoring Circuit for Controlling A Limit Based Parameter Value - Rompis, Lianly (European Journal of Applied Sciences, 2021)
Industrial Revolution 4.0 relates to many digital devices, machines or applications that integrates with internet and needs to be controlled on one or two of its parameter values regarding the importance of output in order to function correctly. Those parameter values have standard limitation and essential automation procedures should be taken for keeping the good operation of devices, machines or system. Controlling a limit based parameter is difficult if done manually and needs full concentration. Digital monitoring circuit would be very helpful for doing that controlling with the support of digital technology development nowadays. The usage of monitoring circuit currently applied in many fields especially for monitoring the condition of a patient in a hospital bed. Regarding health management and digitalization, digital monitoring circuit becomes very important and needs continued improvement. Based on the problem above, this paper is conducted a research to design a digital monitoring circuit for the purpose of controlling a limit based parameter value for patient medication. The research methodology contains literature study, analysis and logic simulation. The outcome derives a reliable digital logic circuit that could be implemented into a real digital circuit or Integrated Circuit (IC) components to help people controlling the condition of a patient based on limit parameter value and support medical industries to improve their devices, machines or system performance to work more accurately and give out best medical services.